SIM.M.T-S2 supplementary bilateral comparison calibration of a reference torque wrench final report - Galvan, J J; Torres-Guzman, J C; Arias, J A; Betancur, I D; ARIAS PRIETO, JUAN ALBERTO (IOP Publishing, 2020)
A Regional Metrology Organization (RMO) key comparison on the calibration of a reference torque wrench was carried out between the Centro Nacional de Metrologia (CENAM, Mexico) and the Instituto Nacional de Metrologia (INM, Colombia), between September 2017 and October 2017. The results of this comparison are reported here, along with descriptions of torque standards used by CENAM and INM, and the uncertainty budget for these standards. This report also describes the protocol for the comparison and presents the data acquired. The results are analyse, determining the degree of equivalence between the torque measurements from CENAM and INM. Main text To reach the main text of this paper, click on Final Report . Note that this text is that which appears in Appendix B of the BIPM key comparison database kcdb.bipm.org/ . The final report has been peer-reviewed and approved for publication by the CCM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).